SUBALTERNISM IN OODGEROO NOONUCCAL’S SELECTED POEMS - Wardatul Khoiriyah; Siti Masitoh; Sri Muniroch (English Letter Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
This study focuses on the subalternism in Oodgeroo Noonuccal’s selected poems. The approach used in this research is post-colonial approach, which focused on the context of literary works contained the effects of colonialism both on societies and cultures. The result of this research shows that the selected poems of Oodgeroo are portraying the subalternism in the matter of the superior domination and the effects which illustrate the British superiority that lead to their domination against Aboriginal people as the weaker party and resulting the great predicaments for them. Woman as subaltern which show how Aboriginal women are forced to be slaves to serve and satisfy the lust of British colonists until the end of their lives. Lastly, the voiceless which show how the Aboriginal people must live surrounding by representations and misrepresentations of the privileged parties who hold domination that makes it more difficult for them to get their rights. This research also revealed that Oodgeroo is successfully speak for the Aboriginal people supported with the fact that she is an Aboriginal woman who write poetry to voice her people.